Evaluation of groundwater resources within Ankpa and environ, north central Nigeria - A.O, Omali; A.O, Usman; Y, Baba (International Journal of Advanced Geosciences, 2020)
Geophysical and Geochemical assessment of groundwater in part of Northern Anambra Basin has been evaluated. The groundwater potentials, aquifer characteristics and groundwater quality within the study area have been delineated. This is aimed is at establishing the depth to watertable and potability of the groundwater within the area. Twenty-(20) vertical electrical soundings (VES) were acquired with a maximum half current electrode spacing of 150 metres using ABEM 4000 SAS Tetrameter. Hydrogeochemical analysis was carried out using HANA Model Hi 83200 multi parameter ion specific meter to evaluate the basic anions and cations in the water samples. Piper, Durov and Schoeller semi-logarithmic plots were drawn to characterize the water types. Results from the geo-electric sections revealed the presence of five to seven geo-electric layers. The depth to water table ranges between 20m and 161.1m. The depth to Watertable is deepest around Ogene area with depth of 161.1m. The result of the geophysical analysis correlates with the borehole data acquired from the study area. Results from hydrogeochemical studies revealed that the concentrations of ions are in the order of Ca2+> Na2+>K+>Mg2+ and HCO3->NO3->SO42->Cl- in Anyigba area, Na2+>K+> Ca2+>Mg2 and Cl- >HCO3->NO3->SO42- Ankpa area while in Ejule area Mg2+>Na2+>K+> Ca2+and Cl- >HCO3->NO3->SO42-. These fall within the WHO (2006) drinking water standard. It is recommended that an average depth of 75m should be drilled for borehole within the northern part of the studied area and a depth of about 100m in the southern part of the study area. In addition, the water is recommended for domestic use.Â Â